Hypersensitivity Reaction to Carbon Fiber-Polyetheretherketone Composite Spinal Implant: A Case Report. Issue 2 (15th April 2022) - Bueno, Brian T.; Henry, Mark; Cho, Samuel K.
Abstract : Case: A 52-year-old woman presented with localized hypersensitivity symptoms immediately after insertion of a carbon fiber-polyetheretherketone (CF-PEEK) vertebral fusion device. After a modified cutaneous patch test confirmed an allergic reaction to the implant, the device was surgically removed. The patient's symptoms were largely resolved 1 month after the removal of the device. Conclusion: CF-PEEK is a commonly used biomaterial in surgical implants. As far as we know, this is the first reported case of a hypersensitivity reaction to CF-PEEK.